SINTESIS MEMBRAN POLIMER ELEKTROLIT DARI BAHAN POLI(VINIL ALKOHOL) DENGAN LITIUM HIDROKSIDA(LiOH) SEBAGAI SUMBER ELEKTROLITNYA - Rahmawati M (PROSIDING SEMINAR KIMIA, 2014)
Electrolyte polymer membranes were synthesized by solution cast method. Fabrication of polymer electrolyte memb ranes done by using the polymer poly (vinyl alcohol)(PVA) and Lithiu m Hydro xide (LiOH) as the source of the electrolyte. PVA dissolved in distilled water while heated at 50 0 C for 2 hours. For preparing LiOH solution, the same procedure as for PVA solution were heated for an hour. Futhermore, PVA solution and LiOH solution were mixed wh ile stirred and heated at 50 0 C for one hour.Then, the mixture solution was evaporated for 2 days which ultimately resulted in a thin sheet-transparent membrane. The perfo rmance of poly mer electro lyte membrane PVA -LiOH characterized by physical properties and conductivity analysis using Electrochemical Impedance Spectroscopy (EIS). The maximum measurement results and conductivity values obtained in 9% concentration of LiOH, reach 2.48 x10 -4 S.cm -1 .